Implantation of an iris-fixated phakic intraocular lens for the correction of hyperopia: 15-year follow-up. Issue 6 (June 2021) - van Rijn, Gwyneth A.; Gaurisankar, Zoraida S.; Saxena, Ruchi; Gibbes, Destiny; Jongman, Henri P.; Haasnoot, Geert W.; Cheng, Yanny Y. Y.; Beenakker, Jan-Willem M.; Luyten, Gregorius P.M.
Abstract : Pigment dispersion might present a problem in hyperopic eyes corrected with an Artisan pIOL lens. A preimplantation anterior chamber depth more than 3.0 mm measured from the corneal endothelium was recommended. Abstract : Purpose: To assess the predictability, efficacy, stability, and safety of implantation of an Artisan iris-fixated phakic intraocular lens (IF-pIOL) for the correction of hyperopia with a follow-up of up to 15 years. Setting: Leiden University Medical Center, the Netherlands. Methods: Patients operated by a single surgeon up to 2007 were identified, and data on refraction, corrected distance visual acuity (CDVA), uncorrected distance visual acuity, endothelial cell (EC) density, and complications were collected. Results: A total of 61 eyes (32 patients) were analysed. The mean spherical equivalent decreased from +6.43 ± 1.78 diopters (D) preimplantation to −0.22 ± 0.57 D at 1 year postimplantation and remained stable throughout follow-up. A stable CDVA with safety indices ranging from 0.91 to 1.10 and efficacy indices between 0.43 and 0.86 were observed. Follow-up time had a significant effect on EC density with an estimated annual decline of 58 cells/mm 2 after IF-pIOL implantation. IF-pIOL explantation was performed in a 10 eyes (16.4%) after 8.13 ± 5.11 years. The main reason for IF-pIOL explantation was EC loss (4 eyes [6.6%]). Pigment dispersion was the most encountered complication, observed in 9 eyes (14.8%). Conclusions: Visual and refractive results after implantation of an IF-pIOL to correct hyperopia show favorable and stable results with long-term follow-up. Lifelong monitoring of EC counts is mandatory. Pigment dispersion might be a problem in hyperopic eyes implanted with an IF-pIOL; a shallower anterior chamber depth and a convex iris configuration might be predisposing factors.